The Influence of Social Media Marketing on Purchasing Decisions is Influenced by Brand Awareness in Avoskin Beauty Products - Mutiara Dini, Ananda; Abdurrahman, Agus (Publisher Cv. Inara, 2023)
Companies in any field must have a strategy that focuses on maintaining the existence of their brand so that it is increasingly recognized by the public. One of the strategies used is through social media marketing. This research aims to analyze the effect of three marketing strategy components on Avoskin Beauty skin care products. This research was conducted using a google form and a questionnaire distributed online. The research also required 160 respondents, this study used a quantitative method with data processing using PLS-SEM (smartpls). The results of this research test will provide answers to the results of the three activity components, namely social media marketing has a positive effect on purchasing decisions, brand awareness has no effect on purchasing decisions, and the last is the influence of social media marketing on purchasing decisions which has a positive effect on brand awareness.